THE UTILIZATION OF CINNAMON (CINNAMOMUM CASSIA) AS A NATURAL MEDICINE FOR DIABETES MELLITUS TYPE 2: SYSTEMATIC REVIEW - Nabila, Ananda; Amalia, Rahma Ahsani; Widiati, Veronika Mutiara; Saryono, Saryono (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Introduction: Diabetes mellitus is a metabolic disorder characterized by high blood glucose levels because the body cannot release or use insulin adequately. Diabetes mellitus has become a health problem whose prevalence continues to increase in society. WHO estimates an increase in the number of people with diabetes mellitus in Indonesia from 8.4 million in 2000 to about 21.3 million in 2030. One of the natural remedies that can be used to lower blood sugar levels is cinnamon (Cinnamomum cassia). Purpose: This systematic review aims to find out the effectiveness of cinnamon use against blood sugar reduction in people with diabetes mellitus. Methods: Journals are derived from electronic databases such as Google Scholar, PubMed and Science Direct, published from 2017 to 2021. Keywords used: cinnamon, diabetes mellitus, and benefits. Discussion: Bioactive content in cinnamon, flavonoids, can lower blood sugar levels by affecting glucose and insulin function in the body. The action mechanism of cinnamon by increasing the sensitivity of insulin receptors includes activating 3-kinase P1 receptors and inhibiting tyrosinfosfatase, increasing the concentration of the fossilized IRS-1 substrate and its binding to 3-kinase PI, activating syntaseglyogen, stimulating glucose uptake, and activating kinase from insulin receptors. Conclusion: After a review of 7 journals, it can be concluded that the administration of cinnamon has the potential to lower blood sugar levels in patients with type-2 diabetes mellitus.